Maternal hypothyroidism in the perinatal period and child development - Agnieszka Strączyńska (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Thyroid hormones are essential growth and development regulators in both foetal and neonatal period. They are involved in metabolic processes, in maturation of nerve and skeletal tissue and many other fluid tissues. Abnormalities in their function during foetal development may have an impact on disorders in pregnancy, or increase susceptibility to the occurrence of neurodevelopmental disabilities in children later in life. There are many observational and epidemiological studies investigating the relationship between maternal thyroid dysfunction and a child development, yet a discussion on the subject is ongoing and robust evidence for its existence is still lacking.